Aryl hydrocarbon receptor controls skin homeostasis, regeneration, and hair follicle cycling by adjusting epidermal stem cell function. (23rd August 2021) - Rico‐Leo, Eva María; Lorenzo‐Martín, Luis Francisco; Román, Ángel Carlos; Bustelo, Xosé Ramón; Merino, Jaime María; Fernández‐Salguero, Pedro María
Abstract: Skin integrity requires constant maintenance of a quiescent, yet responsive, population of stem cells. While interfollicular epidermal progenitors control normal homeostasis, hair follicle stem cells residing within the bulge provide regenerative potential during hair cycle and in response to wounding. The aryl hydrocarbon receptor (AhR) modulates cell plasticity and differentiation and its overactivation results in severe skin lesions in humans. However, its physiological role in skin homeostasis and hair growth is unknown. Reconstitution assays grafting primary keratinocytes and dermal fibroblasts into nude mice and 3‐D epidermal equivalents revealed a positive role for AhR in skin regeneration, epidermal differentiation, and stem cell maintenance. Furthermore, lack of receptor expression in AhR−/− mice delayed morphogenesis and impaired hair regrowth with a phenotype closely correlating with a reduction in suprabasal bulge stem cells (α6 low CD34 + ). Moreover, RNA‐microarray and RT‐qPCR analyses of fluorescence‐activated cell sorting (FACS)‐isolated bulge stem cells revealed that AhR depletion impaired transcriptional signatures typical of both epidermal progenitors and bulge stem cells but upregulated differentiation markers likely compromising their undifferentiated phenotype. Altogether, our findings support that AhR controls skin regeneration and homeostasis by ensuring epidermal stem cell identity and highlights this receptor as potential target for the treatment of cutaneous pathologies. Abstract : Aryl hydrocarbon receptor (AhR) is required for skin homeostasis and hair growth. AhR depletion in keratinocytes and dermal fibroblasts compromises skin regeneration likely because of reduced epidermal stem cells (EpdSCs) numbers. Reconstitution assays suggest a cell autonomous role for AhR in the epidermis. Signaling networks controlling skin homeostasis are AhR regulated in EpdSCs. AhR modulation by physiological ligands may represent a strategy to treat skin pathology.